2019
DOI: 10.1029/2018ja026103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Deep Ingression of the Midlatitude MSTID Into As Low as ~3.5° Magnetic Latitude

Abstract: An observational evidence of medium‐scale traveling ionospheric disturbances (MSTIDs) reaching to magnetic latitude as low as ~3.5° over the Indian sector is provided for the first time based on OI 630‐nm airglow imaging observation from a low‐latitude station, Gadanki (13.5°N, 79.2°E; 6.6° magnetic latitude), on 12 January 2016. The horizontal wavelength, horizontal phase velocity, and period of the MSTID are found to be 160 ± 6 km, 138 ± 14 m/s, and 19.5 ± 3 min, respectively. These phase fronts are observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Mendillo et al (1997) were the pioneers in detecting MSTIDs using all-sky imagers to observe the thermospheric OI 630.0-nm airglow emission. Since then, this optical technique has been widely used to obtain two-dimensional images of these events in the upper atmosphere (e.g., Amorim et al, 2011;Duly et al, 2013;Garcia et al, 2000;Martinis et al, 2010;Pimenta et al, 2008;Seker et al, 2011;Sivakandan et al, 2019).…”
Section: The Arecibo Observatory Rofmentioning
confidence: 99%
“…Mendillo et al (1997) were the pioneers in detecting MSTIDs using all-sky imagers to observe the thermospheric OI 630.0-nm airglow emission. Since then, this optical technique has been widely used to obtain two-dimensional images of these events in the upper atmosphere (e.g., Amorim et al, 2011;Duly et al, 2013;Garcia et al, 2000;Martinis et al, 2010;Pimenta et al, 2008;Seker et al, 2011;Sivakandan et al, 2019).…”
Section: The Arecibo Observatory Rofmentioning
confidence: 99%
“…In order to visualize the spatial and temporal evolution of the airglow emission depletion, keograms are constructed using arbitrary and residual airglow emission intensities (residual intensity derived method is discussed in section ) that is shown in Figure . Detailed description about the keogram analysis is available in literature (Sivakandan et al, ). Figures a and b show the geographic EW and NS keograms (hereafter NS means geographic NS) in terms of total intensity (in arbitrary units) and the Figures c and d show the EW and NS keograms in terms of residual intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, even if EPBs can map up to the mid latitudes on few occasions (Otsuka et al, ; Ma & Maruyama, ; Huang et al, ; Li et al, , ; Aa et al, ; Cherniak et al, ), especially during geomagnetically disturbed conditions, the propagation direction can be used to differentiate EPB and MSF. Consecutively, recent works showed that MSTIDs can ingress very deep into low‐latitude ionosphere (Sivakandan et al, ). However, to the best of our knowledge, MSF structures at the equatorial edge of the mid‐latitude have not been reported so far over the Indian sector.…”
Section: Introductionmentioning
confidence: 99%
“…Because they constitute the main source of ionospheric variability at midlatitudes, it was long thought that MSTIDs were confined in such regions. However, Sivakandan et al () observed MSTIDs originating from midlatitude that reached the equatorial region during nighttime conditions. In low‐latitude regions, beside MSTIDs whose the origin is due to AGWs, it exists other structures sharing morphological similarities with MSTIDs which are called upwellings.…”
Section: Introductionmentioning
confidence: 99%